Effect of booster doses of poliovirus vaccine in previously vaccinated children, Clinical Trial Results 2013. Issue 33 (19th July 2016) - Habib, Muhammad Atif; Soofi, Sajid; Mach, Ondrej; Samejo, Tariq; Alam, Didar; Bhatti, Zaid; Weldon, William C.; Oberste, Steven M.; Sutter, Roland; Bhutta, Zulfiqar A.
Highlights: A study that describe polio vaccine combinations to reach maximum population level immunity. IPV induces significantly higher immune response compared to OPV. IPV has shown the ability to efficiently close existing immunity gaps. Abstract: Background: Considering the current polio situation Pakistan needs vaccine combinations to reach maximum population level immunity. The trial assessed whether inactivated poliovirus vaccine (IPV) can be used to rapidly boost immunity among children in Pakistan. Methods: A five-arm randomized clinical trial was conducted among children (6–24 months, 5–6 years and 10–11 years). Children were randomized in four intervention arms as per the vaccines they received (bOPV, IPV, bOPV + vitamin A, and bOPV + IPV) and a control arm which did not receive any vaccine. Baseline seroprevalence of poliovirus antibodies and serological immune response 28 days after intervention were assessed. Results: The baseline seroprevalence was high for all serotypes and the three age groups [PV1: 97%, 100%, 96%, PV2: 86%, 100%, 99%, PV3: 83%, 95%, 87% for the three age groups respectively]. There was significantly higher rate of immune response observed in the study arms which included IPV (95–99%) compared with bOPV only arms (11–43%), [ p  < 0.001]; Vitamin A was not associated with improved immune response. Immune response rates in the IPV only arm and IPV + bOPV arm were similar [ p  > 0.5]. Conclusion: IPV has shown the ability to efficiently close existing immunity gaps in a vulnerable population of children in rural Pakistan.